The Impacts of Ethics Education on Future Managers’ Ethical Decisions (Journal of Governance and Development (JGD), 2018)
The rise of unethical behaviour like commercial crimes has become an issue and started gaining attention from the government, society and business. Education is seen by scholars as one of the best solutions because it has the ability to produce a holistic result. By educating young generations, who are our future leaders, it will help to awake the interests of people towards building an ethical society. The government of Malaysia started the process of building ethical society by directing all the public universities incorporating ethics education in their curriculum. Universiti Utara Malaysia (UUM) is also committed in realising this agenda. However, since the policy was implemented, there appears to be very minimal research that has explored the effects of ethics education on future managers’ ethical behaviour including in making ethical decisions. Therefore, this paper aims to study the impact of ethics education on future managers’ ethical decisions. A total of 300 students who were in the second-year and third-year studies from various academic programs have been chosen as respondents. From the survey, 78% (n=234) of respondents completed a course on ethics while 22% (n=66) of respondents will taking their ethics courses in the coming semester. This research revealed that the majority of students recognised the importance of ethics and they found that learning ethics was helpful in improving their ethical understanding and developing their personal ethical values. However, practicing ethical values, including making ethical decisions were challenging as students perceived they were living in unethical environment. The respondents indicated that they were surrounded by unethical people, and for this reason, some of them disclosed that they would rather silent than reveal about unethical actions.